PENGARUH VARIASI LATIHAN TERHADAP KETERAMPILAN MAE GERI CHUDAN PADA MAHASISWA PENJAS ANGKATAN 2016 - Juliansyah, Diki; Simanjuntak, Victor G; Hidasari, Fitriana Puspa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThe Purpose of this research is to determine the effect of variations of training on the skills of Mae Geri Chudan on 2016 Physical Education students.This research is an experimental study, a form of pre-experimental design (nondesigns). The instrument used this study was to use the rubric for assessing the basic techniques of Mae geri chudan. The sampling of the population is 70 people was carried out systematically random sampling, with the total sample is 20 people. The results of this study indicate there is the effect of Variation of Exercise on the Skills of Mae Geri Chudan on 2016 Physical Education students.. This is evidenced by the results of the t-test, a significant level of Ftable 5% (0.05), 2.15 with a t-count value (24, 57)> t table (1,72913), which shows an alternative hypothesis is accepted. This it can be concluded that there is the effect of Variation of Exercise on the Mae Geri Chudan Skills on the 2016 Physical Education students. Proven by calculating the percentage increase of 25.81%. Keywords : Effect, Mae Geri Chudan, Variations of Training